Sports fear psychology in martial arts athletes' physical conflict psychology - Cheng, Nan (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
This study aims to investigate the fear of sports psychology in the physical confrontation of Chinese Wushu athletes. This article profiles 40 Chinese students majoring in physical education, and social sports enrolled in a unique martial arts program. The age range is between 19 and 21. The causes of dread among 40 Sanda athletes were investigated using the research methodologies of literature data, interviews, and questionnaire survey. SPSS l4.0 statistical software was utilized to analyze the questionnaire data. Before two competitions following the experiment, students' psychological readiness was evaluated using a psychological exam. The length of the experiment was eighteen weeks. P<0.05 indicated a substantial difference between the test and control groups to aid Sanda athletes in actual fighting. Provide theoretical support for the psychology of fear. Fear of harm, actual battle experience, and insufficient physical reserve are the causes of the fear of psychology in athletes, which can be overcome through a simulation-based training strategy. The management should develop the special sports quality of sanda athletes, rationalize combat and combat training, enhance technical and tactical skills, and bolster psychological training.